Experimental studies of short concrete reinforced steel fiber beams under bending - HERSCOVICI,H. L. (2019)
Abstract This paper presents the results of a test program on 24 concrete beams with a cross section of 15 x 15 cm. Those are divided into two groups of 12 beams. Group I has a steel fiber content of 40 kg/m³ while Group II uses 60 kg/m³ of steel fibers. The tests consider three sets of beam lengths: 300 mm, 500 mm and 800 mm. The beams were submitted to bending aiming at investigating shear stresses, bending, strain energy, toughness, scale effect and fracture energy. Group II showed a slightly higher resistance to rupture than Group I. However, the smaller the length, the larger the influence of the fiber content. The largest fiber content gave the concrete higher resistance when submitted to bending and shear, especially for the smaller lengths. Both strain and fracture energy, however, show considerable differences for smaller lengths, but are almost the same for the 800 mm beams. Toughness shows improvement in the longer beams and a reduction of this property in the shorter beam from Group II.